The Role of Exercise-Induced Arousal and Exposure to Blue-Enriched Lighting on Vigilance - Barba, Antonio; Padilla, Francisca; Luque-Casado, Antonio; Sanabria, Daniel; Correa, Ángel (Frontiers in Human Neuroscience, 2018)
It is currently assumed that exposure to an artificial blue-enriched light enhances human alertness and task performance, but recent research has suggested that behavioural effects are influenced by the basal state of arousal. Here we tested whether the effect of blue-enriched lighting on vigilance performance depends on participants’ arousal level. Twenty-four participants completed four sessions (blue-enriched vs. dim light x low vs. high arousal) at 10 pm on four consecutive days, following a repeated-measures design. Participants’ arousal was manipulated parametrically through the execution of a cycling task at two intensities (low vs. moderate), and was checked by monitoring their heart rate. On each session, distal and proximal skin temperatures were recorded as a neuroergonomic index of vigilance, while participants performed a 20-min psychomotor vigilance task (PVT) under either blue-enriched light or dim light conditions. The Positive and Negative Affect Schedule (PANAS), Karolinska Sleepiness Scale (KSS) and Borg Rating of Perceived Exertion Scale (RPE) were used to measure subjective psychological state. The results showed that the exercise-induced manipulation of arousal produced robust alerting effects in most measures, while the lighting manipulation only attenuated subjective sleepiness and enhanced positive affect, but it did not influence behaviour or physiology. Acute exposure to a blue-enriched light was practically ineffective when the arousal level was over baseline. The present research favoured the use of acute physical exercise over acute exposure to blue-enriched lighting in order to boost humans’ alertness when necessary, as in work settings where maintaining optimal levels of attention is difficult (shift work, night-work, vigilance tasks) and necessary to prevent human error and accidents.